2016
DOI: 10.1371/journal.pone.0159778
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Bile Salt Export Pump (ABCB11) Interactome Employing Complementary Approaches

Abstract: The bile salt export pump (BSEP, ABCB11) plays an essential role in the formation of bile. In hepatocytes, BSEP is localized within the apical (canalicular) membrane and a deficiency of canalicular BSEP function is associated with severe forms of cholestasis. Regulation of correct trafficking to the canalicular membrane and of activity is essential to ensure BSEP functionality and thus normal bile flow. However, little is known about the identity of interaction partners regulating function and localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…WDR83OS is a ubiquitously expressed, predicted transmembrane protein evolutionarily conserved in Caenorhabditis elegans and Drosophila melanogaster. It is reported to interact with the Parkinson's disease P-type ATPase ATP13A2/PARK9 (101) and with the bile acid transporter ABCB11/BSEP (102). A homozygous splice site mutation in WDR83OS has been associated with a syndrome, including hypercholanemia, intractable itching, intellectual disability, and dysmorphic features (103).…”
Section: Crispr-screen Identified Genes Essential For Trpc6 Functionmentioning
confidence: 99%
“…WDR83OS is a ubiquitously expressed, predicted transmembrane protein evolutionarily conserved in Caenorhabditis elegans and Drosophila melanogaster. It is reported to interact with the Parkinson's disease P-type ATPase ATP13A2/PARK9 (101) and with the bile acid transporter ABCB11/BSEP (102). A homozygous splice site mutation in WDR83OS has been associated with a syndrome, including hypercholanemia, intractable itching, intellectual disability, and dysmorphic features (103).…”
Section: Crispr-screen Identified Genes Essential For Trpc6 Functionmentioning
confidence: 99%
“…However, using this method, we did not identify the few other known partners of ABCB4 [18]. This could be explained by: i) a weak sensitivity of the technique; ii) the stringent conditions of the immunoprecipitation; or iii) the poor overlap of the different techniques and studies, as already reported for the analysis of ABCB11 interactome [30]. RAB10 belongs to the RAB protein family, known as key players in intracellular traffic processes [19].…”
Section: Discussionmentioning
confidence: 78%
“…Numerous accessory factors were described to facilitate the translocation process, including the translocating chain-associated membrane protein (TRAM) and the translocon-associated protein (TRAP) [ 7 ]. Interestingly, TRAM and three subunits of the TRAP complex (SSR1, SSR3 and SSR4) were found to interact and coprecipitate specifically with ABCB11 [ 8 ].…”
Section: Folding and Glycosylation Of Canalicular Abc Transportersmentioning
confidence: 99%
“…Another key component of the quality control system is the B-lymphocyte receptor-associated protein (BAP), which was shown to control the folding state and sorting of many proteins in the ER [ 19 , 20 ]. The BAP29 and BAP31 isoforms were described to interact with the N-terminal domain of ABCB1 and ABCB11, respectively [ 8 , 21 ]. More interestingly, it has been shown that some mutations in the BAP31 gene are associated with liver dysfunction and cholestasis [ 22 ].…”
Section: Folding and Glycosylation Of Canalicular Abc Transportersmentioning
confidence: 99%
See 1 more Smart Citation